Probability of occurrence of drought in various sub-divisions of India (MAUSAM, 2001)
There are many studies dealing with interannual variability of rainfall in India. There are also studies available dealing with the reduction of food grain production during various drought years in India, Hence, there is along felt need to know about chances whether the next year will be a drought year. It is also seen that during last 11 years when the country as a whole experienced normal rainfall, there were few sub-divisions almost in each year facing a drought situation. The objective of this paper is to find out with the help of nearly 125 years data the probability of occurrence of drought in various sub-divisions of India and the probability of a sub-division facing two or more consecutive droughts, many studies deal with deficiency in all India summer monsoon rainfall and their linkage with El Nino. Effort has also been made in this paper to find out if there is any linkage between El Nino events in Pacific and meteorological drought in various sub-divisions of India. It is seen that eff~t of El Nino on each sub-division of India is different. It is also noticed that all El Nino years are not drought years and all drought years are also not El Nino years. During last 124 years there were 29 El Nino years. Out of these only 14 were drought years. Similarly there were 25 drought years during last 124 years out of which 11 drought years were not connected with El Nino.